2008
DOI: 10.1245/s10434-008-9923-0
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life Outcomes in Disease-Free Survivors of Mid-Low Rectal Cancer After Curative Surgery

Abstract: Overall, patients with rectal cancer recover well in the long run, with HRQOL levels comparable to that of the general population. HRQOL outcomes provide valuable data that may be used to improve information disclosure to patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
51
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 32 publications
10
51
0
Order By: Relevance
“…Similar results were found in other studies with longitudinal QOL measurements [27][28][29] and confirmed by a systematic review of 23 studies regarding the changes in physical-and role functioning after colorectal cancer treatment [30]. Also, worse postoperative physical functioning in older patients compared to younger patients was described previously [7,[32][33][34][35][36][37]. Our results may add that older patients still report poor physical-, social-, and role functioning up to one year after diagnosis compared to their pretreatment level and compared to the reference population, indicating slow recovery or permanently affected functioning.…”
Section: Discussionsupporting
confidence: 88%
“…Similar results were found in other studies with longitudinal QOL measurements [27][28][29] and confirmed by a systematic review of 23 studies regarding the changes in physical-and role functioning after colorectal cancer treatment [30]. Also, worse postoperative physical functioning in older patients compared to younger patients was described previously [7,[32][33][34][35][36][37]. Our results may add that older patients still report poor physical-, social-, and role functioning up to one year after diagnosis compared to their pretreatment level and compared to the reference population, indicating slow recovery or permanently affected functioning.…”
Section: Discussionsupporting
confidence: 88%
“…Although the mean QoL scores reported within this study are comparable to population norms [3][4][5], pain was significantly associated with poorer SRH and QoL on all subscales. Furthermore, differences in FACT-C scores between those who did and did not report pain are clinically significant, with disparities greater than the minimally important differences suggested by Yost and colleagues [23].…”
Section: Discussionsupporting
confidence: 49%
“…Previous studies concluded that colorectal cancer (CRC) survivors regain quality of life (QoL) of similar or greater levels than those reported by normative populations [3][4][5]. The positive reframing of QoL in the presence of chronic symptoms is a widely discussed and accepted concept within the chronic illness literature [3,6].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to surgery alone, however, this approach is associated with increased male sexual problems, faecal incontinence, and bowel dysfunction, which, in turn, negatively affect the quality of life of patients [3,4].…”
Section: Introductionmentioning
confidence: 99%